PENGARUH PENGETAHUAN DAN POLA ASUH ORANG TUA TERHADAP STUNTING PADA BALITA DI KP MADANGKARA RW 16 KELURAHAN SAWAH GEDE KECAMATAN CIANJUR KABUPATEN CIANJUR - Diajeng Maya Mumtahanah; Muhamad Fadel Abdulah; Muhammad Luthfi Aziz; Naufal Haidar; Sina Delphia; Sukmana Sufia Dwi Ambarini; Tri Dimas Wandanu Febriansyah (BAKTIMU : Jurnal Pengabdian Kepada Masyarakat, 2023)
Cianjur is included in the district that enters the red zone of stunting prevalence with a percentage of 33%. The stunting rate in Cianjur Regency exceeds the set tolerance rate or is above 30%. This study aims to analyze the effect of parental knowledge and parenting patterns on stunting in toddlers at KP Madangkara RW 16, Sawah Gede Village, Cianjur District, Cianjur Regency. The type of this research is using an analytic observational research with a Cross-Sectional Study approach. The population in this study are 46 children in KP Madangkara RW 16 SawahGede Village, Cianjur District, Cianjur Regency in 2022. Then it was reduced again using the Purposive Sampling Technique to a total of 30 children, which was seen based on the inclusion and exclusion criteria. The results of the bivariate analysis carried out, it can be seen that the value of r square is 0.842. This means that knowledge (X1) and parenting patterns (X2) simultaneously affect stunting (Y) by 84.2%. In conclusion, there is an influence of knowledge and parenting patterns on stunting in toddlers in KP Madangkara RW 16, Sawah Gede Village, Cianjur District, Cianjur Regency.Keywords: Knowledge, Parenting patterns, Stunting